Pengaruh Profitabilitas, Leverage Dan Likuiditas Terhadap Islamic Social Responsibility (ISR) - Irvan Ali Mustofa; Saiful Nggufron Efendi; Diana Elvianita Martanti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Every company focuses on achieving high profits. One way a company can achieve this is by creating a positive image in the community by paying attention to the environment or its social responsibilities, through practices commonly known as Corporate Social Responsibility (CSR). Therefore, banks are service companies whose success depends on the trust placed in them by customers in implementing corporate governance and CSR. The Corporate Social Responsibility (CSR) index was created in line with the need for disclosure of social performance in Indonesian banking. This study seeks to identify the factors that determine the level of CSR of Islamic banks in Indonesia. The expansion of corporate social responsibility is viewed from an Islamic perspective as adding another aspect to financial reporting. In Indonesia, Islamic banks are increasingly using Islamic Social Responsibility (ISR). Based on their annual reports, Indonesian banks listed on the Indonesia Stock Exchange attempt to measure the factors influencing ISR. Profitability, leverage, and liquidity are three variables used to examine the factors that determine ISR. To assess ISR, we examined the annual reports of Islamic banks from 2021 to 2023. Data were collected from the Indonesia Stock Exchange directory using documentation techniques. Using panel data and multiple regression analysis, we found that the ISR is significantly influenced by profitability, leverage, and liquidity. These results provide a new perspective on corporate reporting from a religiosity perspective.